2000
DOI: 10.1046/j.1365-2303.2000.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of smear taking practice in the former North Thames region

Abstract: One hundred and seventy-seven doctors and 161 nurses from 230 clinics responded to a questionnaire on smear taking practice. The responses show that 66% of smear takers use the Aylesbury spatula and 30% use the Ayre spatula. A total of 53% use a cytobrush for selected cases. Training of smear takers and preparation of smears was satisfactory. Most (but not all) smear takers routinely record clinical information on the request form. Only 20 cytology laboratories in the North Thames region (70%) provide addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…However, as yet there is little agreement on an accepted performance indicator for smear takers. Whilst there is general agreement on the need to audit performance and provide feedback, 2,5,[9][10][11] the actual format recommended ranges from Ôpick upÕ rates 12 to TZ sampling rates 13 and unsatisfactory smear rates 10,14 for individual practitioners. It is generally agreed that the two yearly audit of unsatisfactory smear rates (for conventional smears) as is recommended by the General Medical Services (GMS) 14 offers limited useful information on clinical ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as yet there is little agreement on an accepted performance indicator for smear takers. Whilst there is general agreement on the need to audit performance and provide feedback, 2,5,[9][10][11] the actual format recommended ranges from Ôpick upÕ rates 12 to TZ sampling rates 13 and unsatisfactory smear rates 10,14 for individual practitioners. It is generally agreed that the two yearly audit of unsatisfactory smear rates (for conventional smears) as is recommended by the General Medical Services (GMS) 14 offers limited useful information on clinical ability.…”
Section: Discussionmentioning
confidence: 99%
“…He proposed that the comparison of TZ sampling rates achieved by smear takers sending samples to the same laboratory was a useful performance indicator – a view which echoed those of Curtis et al. , 4 who cited the presence of TZ cells as one of the main criteria that reflects clinical proficiency, and Awadhi and Coleman who suggested that periodic feedback to clinicians and smear takers has an important role in improving performance in health care 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Most trainees were either fairly or very confident about the practical aspects but not about the theoretical aspects of cervical smear taking. 13,14 Most trainees were either fairly or very confident about the practical aspects but not about the theoretical aspects of cervical smear taking.…”
Section: Discussionmentioning
confidence: 99%
“…The number of trainees with assigned smear takers numbers was small (12%) thus reducing the ability to audit individual practice both in terms of training accreditation and ongoing practice, and to facilitate feedback and identification of those requiring updating. 13,14 Most trainees were either fairly or very confident about the practical aspects but not about the theoretical aspects of cervical smear taking. This is in accordance with the fact there was a lack of formal training.…”
Section: Discussionmentioning
confidence: 99%